Significance of the Fezzan Region in French Policy in Libya and the Sahel - A. M. Nadzharov (Международная аналитика)
For a hundred years, since the French colonization of Chad and Niger, the Libyan region of Fezzan has played a signiﬁcant role in the French strategy in Africa. The determining factor in the importance of the region for the policy of Paris was played by the transnational processes of the Fezzan border. The ethnic proximity of Fezzan and the northern regions of the Sahelian countries catalyzed the Franco-Libyan clashes in Chad in the 1900s, when the colonialists faced the resistance of the Senussi order, which was suppressed only with the beginning of the Italian conquest of Libya. The desire of Paris to establish control over the region to ensure the security of its possessions in the Sahel and their connection with the Algerian departments formed the basis of its policy in the middle of the 20th century. The signiﬁcant inﬂuence of the region on the Sahel after decolonization prevailed, most clearly manifested in the 1970s and 1980s, when the Libyan Arab Republic tried to use ethnic contradictions in Chad to establish its hegemony in the north of the country, which, in turn, led to a conﬂict with Paris, in which the Fifth Republic, thanks to skillful work with the tribes of the Libyan-Chadian borderlands. After the outbreak of the civil war in Libya in 2011, Fezzan regained its importance for French politics due to the emergence in the region of terrorist structures associated with transnational Sahelian crime, the Chadian opposition and the forces of other great powers. The article examines the patterns of the French strategy towards Fezzan, in particular the French security policy in the Fezzan borderlands. The study of the historical retrospective of French politics allows us to more thoroughly determine the motives and intentions of the strategy of the Fifth Republic in southwestern Libya at the present stage.